Organizational behavior in sport management - MacIntosh, Eric W. 1977-; Burton, Laura J. (Human Kinetics, 2019)
Organizational Behavior in Sport Management covers issues such as diversity, ethics, values, behavior, leadership, and much more, giving students insights into key contemporary topics in the field. Organizational Behavior in Sport Management offers the following features: learning objectives and discussion questions for each chapter that help students conceptualize, retain, and understand the content; case studies with discussion questions to help students apply the concepts from each chapter; in the boardroom sidebars that use real-life examples from organizations within the field to highlight key topics. Organizational Behavior in Sport Management presents classical research in organizational behavior and up-to-date knowledge from the field of sport management. The authors offer information on individual, intrapersonal, and organizational processes that are fundamental to working within a sport organization, placing equal emphasis on what managers of sport organizations need to understand about human behavior and what each person brings to the work situation in terms of his or her attitudes, thoughts, perceptions, and skills. This text answers the key questions of why we do what we do at work, why others behave as they do, and how our interpretation of events and behaviors is subject to our own biases. Students will explore the most important topics in organizational behavior and get a glimpse of how they could successfully function in a sport organization